Think Different The Merits of Unconscious Thought in Preference Development and Decision Making.(article). - Dijksterhuis, Ap.
The role of unconscious and conscious thought in decision making was investigated in 5 experiments. Because of the low processing capacity of consciousness, conscious thought was hypothesized to be maladaptive when making complex decisions. Conversely , unconscious thought was expected to be highly effective . In experiments participants presented with a complex decision problem in which they had to choose between various alternatives. Each with multiple attributes. Some participants had to make a decision immediately after being presented with the options. In the conscious thought conditions, participants could think about the decision for a few minutes . In the unconscious thought conditions, participants were distracted for a new minutes and then indicated their decision. throughout the experiments, unconscious thinkers made the best decisions. Additional evidence obtains in Experiments 4 and 5 suggests that unconscious thought leads to clearer , more polarized and more integrated representations in memory. -- (from the author).
Keywords: Psychology-Periodicals.